A gamificação como recurso estratégico de marketing de conteúdo: estudo de caso do fantasy game Cartola FC - Batista, Aron Rodrigo de Carvalho (2018)
The present work is about an area of study that has been explored intensively in several fields of knowledge in recent years, gamification. We tried to analyze the marketing strategies present in the fantasy game Cartola FC, considering the interaction and interactivity within the game itself and its different official platforms in the media and social networks that allow a greater contact between brand and consumer. The fantasy game was followed from June to December 2017. We start from the following research problem: Does gamma-based marketing strategies, through a Fantasy Game, improve interactivity between users and web platforms? In order to answer this question, the theoretical basis adopted includes the theoretical conceptions of Torres (2009), Aarseth (2011), Werbach and Hunter (2012) and Hemley (2012), based on Richard Bartle's division. To deal with the concept of marketing Kotler (2003) became important in this work. Santaella (2013), Reis (2015) and Favaro Junior (2011) were used to deal with gamification and on Cartola FC himself. As a general objective, we sought to identify and classify the marketing actions used in the fantasy game Cartola FC, verifying the question of the interactivity provided by the object. As a methodological resource, a qualitative and descriptive approach was adopted, having as a method of analysis, the case study. At the end of this work it is concluded that Cartola FC uses important digital marketing strategies of the present time, from the main one, the Gamification, focus of this work. It was also observed the functioning of these aspects in the game and the commitment with which the fantasy management team works on its website and other official communication channels in search of providing a good experience to the users. This can be perceived through the constant updates available, different formats to disseminate content and channels also different from contact between user and brand. Finally, it is considered that given the growing change in the behavior of the mass user of technology, especially of media and social networks, the improvements should not stop there. With this, it is possible to design an even greater popularization of the fantasy game Cartola FC in the next years.